Tudor and Stuart Consorts
XXVII, 369 p. 15 illus., 11 illus. in color.
Keywords: "This important and engaging volume asks crucial questions about the meaning and exercise of power of the Tudor and Stuart consorts. Carefully nuanced studies interrogate the individuality and agency of the women and men—some well-known, others remarkably little studied—who fulfilled this role in the premodern period. Critically, this impressive collection offers a far deeper and much-needed analysis of the office of consort, recognising it as a critical component of early modern monarchy.” –Susan Broomhall, Australian Catholic University, Australia This book examines the lives and tenures of all the consorts of the Tudor and Stuart monarchs of England between 1485 and 1714, as well as the wives of the two Lords Protector during the Commonwealth. The figures in Tudor and Stuart Consorts are both incredibly familiar—especially the six wives of Henry VIII—and exceedingly unfamiliar, such as George of Denmark, the husband of Queen Anne. These innovative and authoritative biographies recognise the important role consorts played in a period before constitutional monarchy: in addition to correcting popular assumptions that are based on limited historical evidence, the chapters provide a fuller picture of the role of consort that goes beyond discussions of exceptionalism and subversion. This volume and its companions reveal the changing nature of English consortship from the Norman Conquest to today. Aidan Norrie is Lecturer in History and Programme Leader at the University Campus North Lincolnshire, UK, and the Managing Editor of The London Journal. Carolyn Harris is Instructor in History at the University of Toronto School of Continuing Studies, Canada, and a regular royal commentator in Canadian media. J.L. Laynesmith is Visiting Research Fellow in Medieval Studies at the University of Reading, UK. Danna R. Messer is Senior Acquisitions Editor at Arc Humanities Press, and the Executive Editor of The Encyclopedia of the Global Middle Ages. Elena Woodacre is Reader in Renaissance History at the University of Winchester, UK, Editor-in-Chief of the Royal Studies Journal, and the founder of the Royal Studies Network.